The Structural Domains of Pseudomonas aeruginosa Phosphorylcholine Phosphatase Cooperate in Substrate Hydrolysis: 3D Structure and Enzymatic Mechanism - Infantes, Lourdes (2012)
Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen. It colonizes different tissues by the utilization of diverse mechanisms. One of these may involve the breakdown of the host cell membrane through the sequential action of haemolytic phospholipase-C and phosphorylcholine phosphatase (PchP). The action of haemolytic phospholipase-C on phosphatidylcholine produces phosphorylcholine, which is hydrolyzed to choline and inorganic phosphate by PchP. The available biochemical data on this enzyme demonstrate the involvement of two choline-binding sites in the catalytic cycle and in enzyme regulation. The crystal structure of P. aeruginosa PchP has been determined. It folds into three structural domains. The first domain harbors all the residues involved in catalysis and is well conserved among the haloacid dehalogenase (HAD) superfamily of proteins. The second domain is characteristic of PchP and is involved in the recognition of the choline moiety of the substrate. The third domain stabilizes the relative position of the other two. Fortuitously, the crystal structure of PchP captures molecules of Bis-Tris at the active site and at an additional site. This represents two catalytically relevant complexes with just one or two inhibitory Bis-Tris molecules and provides the basis of the PchP function and regulation. Site directed mutagenesis along with biochemical experiments corroborate the structural observations and demonstrate the interplay between different sites for choline recognition and inhibition. The structural comparison of PchP with other phosphatases of the HAD family provides a 3D-picture of the conserved catalytic cycle and the structural basis for the recognition of the diverse substrate molecules.